Design analysis of pancanaka 2000 tooth bucket structure using finite element method - Raihan Fadhila; Yosef Budiman; Bambang Sulistyo (Universitas Negeri Yogyakarta, 2025)
This study tests the structural performance of the Pancanaka 2000 tooth bucket, a common heavy-duty excavation component. The goals are to determine the component testing method, analyze the findings of finite element simulation sub-modeling, and identify the causes of structural failure. Shining 3D scanning created a detailed model of the Pancanaka 2000 tooth bucket. ANSYS simulation software performed a Finite Element Analysis on this model. A 10-ton static force was applied to imitate working circumstances on the bucket teeth tip. The simulation monitored mechanical reactions, including total displacement, von Mises stress, and safety factors, which indicate structural reliability. The study found numerous noteworthy findings. First, the computerized model of the bucket teeth allowed for an exact analysis of loading stress. The simulation revealed a region susceptible to failure under high loads, characterized by a maximum total displacement of 0.38883 mm, a maximum von Mises stress of 321.5 MPa, and a minimum safety factor of 1.328. Qualitative analysis identified material as the leading cause of fracture. Wear and scraping were noticed at the bucket tooth-adapter interface. Mechanical failure was also linked to component gaps exceeding design tolerance. These flaws lead to inappropriate load distribution and stress concentration, resulting in structural failure during operation. According to this study, the durability and performance of excavator components, such as the Pancanaka 2000 teeth bucket, depend on correct design, strict material selection, and precise assembly tolerances.